Postoperative of cardiac surgeries: prevalent complications within 72 hours - Danieli Covalski; Eglon Pauli; Alane Karen Echer; Raquel Ribeiro Nogueira; Vera Lúcia Fortunato Fortes (Universidade Federal de Santa Maria, 2021)
Objective: to identify complications in the initial 72 hours after cardiac surgery and their association with clinical and demographic characteristics. Method: this is a cross-sectional study, performed with the analysis of medical records of patients undergoing cardiac surgery between January 2018 and December 2019 in a large hospital. Results: of the 252 medical records evaluated, elderly men were prevalent, assisted by the Unified Health System, with comorbidities, and who used continuous medication. The prevalent type of surgery was single valve replacement and 75.8% of the patients had complications. The most frequent complication was of cardiac origin. Associations were observed between their presence and higher median age, comorbidities, and longer cardiopulmonary bypass, in addition to categorical complications with reintervention and 72-hour mortality and overall. Conclusion: cardiac, renal, electrolyte, pulmonary, hematological and neurological complications were identified, which in some cases are associated with more serious aspects.